Outcome of Conservative Treatment of Odontoid Fractures in Elderly Patients Over 80 Years Old - Speldova, Andrea; Vcelak, Josef; Mirchi, Lukas F; Sedova, Lucie; Seda, Ondrej (Geriatric orthopaedic surgery & rehabilitation, 2025)
INTRODUCTION: The retrospective study evaluated the clinical and radiological outcomes of conservative treatment for type II odontoid C2 fractures in octogenerians. The study aimed to assess the clinical outcomes and quality of survival of patients treated using conservative methods. Additionally, the study sought to define radiological outcomes, fracture healing success and the development of complications in correlation with clinical outcomes. MATERIALS AND METHODS: Patients aged ≥80 with dens C2 fracture were fixed with a hard cervical collar for 6 weeks, followed by early mobilization. Patients showing delayed fracture healing on computed tomography (CT) scan were subsequently immobilized in a soft neck collar for additional 6 weeks. The follow-up CT scan was then performed with consequential rehabilitation. Patients with nonunion of the C2 on the follow-up CT scan and clinical symptoms were contraindicated for physical rehabilitation for cervical spine till next CT scan after another 12 weeks. Clinical and radiographic evaluations were performed during follow-up visits, with a median follow-up was 109 days, with the range extending from 1 day to 1 year. RESULTS: In total, 33 patients were included in the study and were followed for 1 year. The 30-day mortality rate was 21.2%, and between 30 days and one year post-treatment, it was 18.2%. Mortality was higher during the study period in displaced fractures (>2 mm; 9 out of 16 patients died) compared to non-displaced fractures (≤2 mm; 4 out of 17 patients died). The Japanese Orthopaedic Association (JOA) score remained unchanged between admission (mean 16.9; SD ± 0.5) and the end of follow-up (mean 16.9; SD ± 0.5; P > 0.05), the Visual Analogue Scale (VAS) score showed improvement from values measured upon admission to the hospital (mean 7.97; SD ± 1.33) to values measured at the end of follow-up (mean 1.58; SD ± 1.62; P < 0.001) and the Neck Disability Index (NDI) showed a statistically significant difference between admission (mean 41.3; SD ± 14.92) and the end of follow-up (mean 14.29; SD ± 4.65; P < 0.001). The standard measurement of Posterior Atlantodental Interval (PADI) had an average value of 18.6 (range 16-22 mm) and primary bony union of odontoid fractures occurred in eleven cases (33.3%), while six patients (18.2%) had fibrous union with minimal clinical difficulties. CONCLUSION: This study demonstrates the safety and efficacy of conservative treatment for odontoid fractures in octogenerians and underscores the critical role of conservative management in a polymorbid elderly population.